2020
DOI: 10.3390/ijerph17134751
|View full text |Cite
|
Sign up to set email alerts
|

The Matthew Effect in Recovery from Smartphone Addiction in a 6-Month Longitudinal Study of Children and Adolescents

Abstract: The clinical course of problematic smartphone use (PSU) remains largely unknown due to a lack of longitudinal studies. We recruited 193 subjects with smartphone addiction problems for the present study. After providing informed consent, the subjects completed surveys and underwent comprehensive interviews regarding smartphone usage. A total of 56 subjects among the 193 initially recruited subjects were followed up for six months. We compared baseline characteristics between persistent addicted users an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 53 publications
(74 reference statements)
1
19
0
Order By: Relevance
“…Data were collected via self-report measures and were cross-sectional, which precludes any causality statement. Recent studies have used a longitudinal design (Herrero, Torres, Vivas, & Urueña, 2019;Lapierre, Zhao, & Custer, 2019;Lee et al, 2020) or a qualitative approach (Yang, Asbury, & Griffiths, 2019) for the study of smartphone use/dependency or PSU, and further studies that use these alternative methodologies should be conducted to complement our approach. The present study focused on a specific demographic group (i.e., college students with regular access to the Internet, predominantly females), thus limiting the generalisability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected via self-report measures and were cross-sectional, which precludes any causality statement. Recent studies have used a longitudinal design (Herrero, Torres, Vivas, & Urueña, 2019;Lapierre, Zhao, & Custer, 2019;Lee et al, 2020) or a qualitative approach (Yang, Asbury, & Griffiths, 2019) for the study of smartphone use/dependency or PSU, and further studies that use these alternative methodologies should be conducted to complement our approach. The present study focused on a specific demographic group (i.e., college students with regular access to the Internet, predominantly females), thus limiting the generalisability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, many studies have reported a positive association between sleep deprivation and PSU or between poor sleep quality and PSU [ 18 , 22 , 43 ]. Sleep problems such as bedtime phone usage before sleep may not only contribute to the onset of PSU but was shown to act as a prognostic factor for PSU recover [ 44 ]. These results support the hypothesis that smartphone use affects sleep patterns, for example, through light stimulation, which would therefore explain the addictive SB increasing sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study suggested that the quantity and quality of family conversations affected individual PSU [38]. In addition, adolescents who spend significant amounts of time talking with their mothers are more likely to avoid PSU [39]. The current study results indicate that avoiding negative mother-child communication is important to ensure children's correct smartphone use.…”
Section: Discussionmentioning
confidence: 56%